HMGB1 expression in SJS/TEN sera and skin. (1st July 2019) - Carr, D.F.; Wang, C.‐W.; Bellón, T.; Ressel, L.; Nwikue, G.; Shrivastava, V.; Bergfeld, W.; Jorgensen, A.L.; Chung, W.‐H.; Pirmohamed, M.
Summary: Stevens Johnson Syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, severe, skin blistering conditions in which areas of skin die and detach. They actually represent a single disease with a spectrum of severity: less than 10% body surface area detachment in SJS and more than 30% in TEN. It affects around 500 people in the UK each year and is most commonly caused by a reaction to a wide‐range of commonly prescribed drugs. This study brought together researchers and patients from the U.K., Spain, Taiwan and the U.S.A. and aimed to determine levels of a protein called high mobility group box 1 (HMGB1) in the serum (part of the blood), blister fluid and skin biopsy tissue of SJS/TEN patients. HMGB1 is a protein which is known to be a marker (biological sign) of a) tissue/cell injury and b) activation of the immune response, both of which occur in SJS/TEN. The authors detected elevated serum HMGB1 levels in SJS/TEN patients at the time of reaction in three independent patient populations, and also extremely high levels in patients' blister fluid. Levels of HMGB1 in the epidermal (upper) layer of the skin were considerably decreased in SJS/TEN patients but not healthy control or drug‐induced rash skin. The decrease in HMGB1 levels in the epidermis of the skin appears to occur prior to blistering and may represent an early indicator. In addition, levels of HMGB1 appear to be retained at the junction between the epidermis and the next layer of skin, called the dermis, which may suggest a potential role for HMGB1 in the mechanism by which the layers become detached in SJS/TEN patients. The authors conclude that serum HMGB1 may not represent a good clinical marker of SJS/TEN, but that decreased levels of it in the skin may be a sign of the early onset of skin blistering, and could have a key role in the mechanism by which this occurs. Abstract : Linked Article: Carr et al. Br J Dermatol 2019; 181 :166–174